THE EFFECT OF DIFFERENT WAYS OF CHITOSAN COATING ON SMOKED CATFISH (Pangasius hypophthalmus) QUALITY DURING ROOM TEMPERATURE STORAGE - Sari, N. Ira; Sukmiwati, Mery; ', Febriandi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis research was aimed to determine the effect of different ways of chitosan coatingon the quality of smoked catfish (Pangasius hypophthalmus) during room temperaturestorage. The method used in this research was experimental method, with coating of chitosanin different ways to smoked catfish; without treatment (K0), spraying with 2% of chitosanconcentration (K1), and brushing with 2% of chitosan concentration (K2). Smoked catfish wasobserved to organoleptic test appearance, odor, flavor, texture; moisture content, proteincontent, fat content, peroxide value; identification of fungi and bacteria Staphylococcusaureus. The results showed that smoked catfish (Pangasius hypophthalmus) was coated withbrushing 2% of chitosan concentration could slowdown the deterioration smoked catfishquality during room temperature storage, with organoleptic value of appearance, odor, flavor,and texture was 6.78, 6.74, 6.72 and 6.84 respectively. Proximate value, also could slowdownthe deterioration in protein content (34.44% to 29.97%) and fat content (31.60% to 24.39%).Its could inhibit the increasing of moisture content (10.09% to 15.37%) and peroxide value(0.00mg ek/1000g to 7.38mg ek/1000g); the fungus Aspergillus sp and Staphylococcusaureus were not found during room temperature storage.Keywords: smoked catfish (Pangasius hypophthalmus), chitosan liquid, storage.